Edukasi Pengelolaan Sampah dan Literasi Digital Bank Sampah sebagai Upaya Peningkatan Nilai Ekonomi Masyarakat - Prio Kustanto; Mayadi; Ahmad Fathurrozi (Journal Of Computer Science Contributions (JUCOSCO), 2026)
Waste management remains one of the major challenges in urban areas such as Bekasi City, where the volume of household waste continues to increase while most residents still regard waste as having no economic value. In response, Yayasan Cahaya Insan Sejahtera organized a community education program themed "Dari Sampah Menjadi Cuan" (From Waste to Cash) at Gedung MD, Jalan Pulau Timor Raya, RW.09, Aren Jaya Village, East Bekasi, Bekasi City. The event drew participants not only from the surrounding neighborhood but also from several other sub-districts (kelurahan) within East Bekasi, and even from outside the East Bekasi area, reflecting the broad public interest in the topic. This community service activity involved a lecturer from the Informatics study program of Universitas Bhayangkara Jakarta Raya together with two practitioner speakers, Ir. H. Iman Kukuh Santoso (a practitioner in plastic waste management) and Rahman Hakim (a practitioner in organic waste management), delivering education on sorting organic and inorganic waste, converting plastic waste into ecobricks and craft materials, processing organic waste into compost and maggot cultivation, and introducing the role of information technology in supporting waste bank management, including digital recording of member registration, waste deposits, weighing, savings balances, and transaction reports. The activity used a participatory training method consisting of planning, direct education, and evaluation stages. The program is expected to encourage the community to view waste management as both an environmental responsibility and a source of additional household income, while opening opportunities for future development of a digital-based waste bank information system.